Developing a theme-based language course for hotel front-line staff / Rohayu Mohd Yunos..[et al.] - Mohd Yunos, Rohayu; Syed Abdul Rahman, Sharifah Amani; Ismail, Normah (Universiti Teknologi MARA, Kedah, 2013)
This paper reports on a project to develop an ESP (English for Special Purposes) course for a group of hotel front-line staff at an island resort in Malaysia. The course makes use of a theme- based module focusing on language associated with host-guest interaction. The paper describes in detail three phases of the project as well as the results of the needs analysis. Qualitative and quantitative data were gathered through questionnaires and observations. Findings indicate that multifunctional language skills are needed for the hotel staff particularly in relation to understanding and giving information, asking questions and practicing simple hospitality etiquette. Furthermore, activities to enhance staff confidence in speaking English are also equally important. The paper concludes with some practical implications for ESP teachers and trainers who wish to develop an English Language training module for hotel staff.